Evolução de turbiditos e sua mineralização aurífera no lineamento Córrego do Sítio e área Cuiabá-Lamego: geoquímica, geocronologia e in situ LA-ICP-MS em sulfetos - Jorge Geraldo Roncato Junior (2016)
The Rio das Velhas greenstone belt is located in the Quadrilátero Ferrífero district, in the southern extremity of the São Francisco Craton, central-southern part of the State of Minas Gerais, SE Brazil.Turbidite sequences of the greenstone stratigraphy are largely distributed in region, and representm resedimented associations dominated by alternating graywackes and pelites, with parallel to discordant metamafic dikes and sills. The Córrego do Sítio lineament in the eastern sector hosts important turbidite gold deposits. On the other hand, similar rocks overlying the area of the Cuiabá-Lamego BIF-hosted gold deposits are loci only to historical diggings and occurrences, in the northern sector of the Quadrilátero region. A study of geology and rocks paragenesis has been conducted at the Córrego do Sítio auriferous lineament, focusing the Cachorro Bravo, Laranjeiras and Carvoaria turbidite-hosted gold deposits, described to illustrate the essentially similar general character of all the deposits of the eastern sector lineament, where, for the Cachorro Bravo deposit, a geological mapping included two underground mine galleries. Different vein types of veins and veinlets are recognized, but the most important volumetrically is a S1-concordant type characterized by smoky and milky quartz-carbonate-sulfide ± sulfosalts veins. The resedimented mixed and felsic sources of eastern greywackes grade into pelagic sedimentary rocks, while mainly felsic source of northern graywackes are transitional with the volcaniclastic association graywackes. The in situ UPb and Lu-Hf detrital zircon analyses suggest the Rio das Velhas II and Mamona events as main periods of sources for both sectors. Proterozoic ages are also identified as zircon sources for the turbidites sequences, intercalated with the Paleoarchean and Archean data. Variations in Lu-Hf isotope analysessupport the idea that the evolution of the basement was made by crust-mantle mixing processes. In situ LA-ICP-MS analyses of arsenopyrites, pyrites and pyrrhotites from carbonaceous pelites onCórrego do Sítio lineament, display a considerable range of trace element compositions. Two hydrothermal stages are recognized: Early hydrothermal, marked by the development of porous sulphides, during which some gold precipitation took place; Main to late hydrothermal, recognized by the development of smooth sulphides, with gold peaking its values. The As, Co, Ni, Te, Pb and Sb concentration in porous and smooth arsenopyrite from the main stages of gold mineralization hasimportant implications for the exploration of the deposits. The mixed source for the host rocks may explain why gold correlates correlates to Se, As, Sb and Te of sedimentary affiliation, as well as to the mafic-ultramafic elements Co, Ni, and Pt. Arsenic is the most abundant trace element in Aubearing porous and smooth pyrite (P-Py and S-Py) and porous and smooth arsenopyrite (P-Apy and S-Apy), of the Laranjeiras and Cachorro Bravo deposits, followed by Ni and Co. These elements were probably leached during hydrothermal alteration indicating a local metal and fluid source during gold mineralization.